Morphological and Physiological Characterization of Cassava Genotypes on Dry Land of Ultisol Soil in Indonesia - Ridwan Diaguna; null Suwarto; Edi Santosa; Arief Hartono; Gatot Pramuhadi; Nunung Nuryartono; Roza Yusfiandayani; Tri Prartono (International Journal of Agronomy)
Indonesia has a large cassava diversity, but the tolerant cultivars on drought areas have not been well recorded. Candidate mapping can begin with morphological and physiological characterization. This study aimed to map cassava’s genetic diversity, determining the key phenotype to distinguish genotypes, physiological adaptation, and high-yield candidates under environmental stress. A total of 29 genotypes were clustered into 5 groups. A specific group for genotype from same site was not found. The differences and relations among genotypes were very clear, demonstrating cassava’s genetic diversity in Indonesia. The key group characteristics are upward petiole orientation (G1), nine lobes (G2), prominent foliar scars (G3), winding lobe (G4), and elliptic-lanceolate (G5). A total of 19 genotypes had a number of storage root >10 storage roots, 20 genotypes had a weight of storage root >2 kg/plant, and 3 genotypes had >4 kg/plant. Morphological and physiological trait determination is relevant to contribute to high-yield cassava breeding in dry areas. The morphological characteristics of well-adapted plants were plant height, lobe characteristics, and petiole orientation, while the physiological traits were chlorophyll index, transpiration rate, and photosynthesis rate.